Analisis Pola Pembelian Konsumen pada PT Indoritel Makmur Internasional Tbk Menggunakan Metode Algoritma Apriori - Narti Eka Putria; Rika Harman (Prosiding, 2020)
PT Indoritel Makmur Internasional Tbk or better known as Indomaret is one of the companies engaged in retail in which this company every day must meet the needs of consumers. Consumers tend to pay attention to prices on label and product layout. At the price tag, the promo price and promo period are shown. However, when the promo period is still ongoing, the desired product kosumen is empty. In addition, the laying of the product on the shelf is not in accordance with the habits of consumers when buying the product simultaneously in one time. This causes disappointment to consumers who can not meet their needs. Therefore the company should look at the purchase patterns made by consumers. To know the product purchased simultaneously, use association rule (data association rule) that is Data Mining technique to find association rule of a combination of items. The association search process uses the apriori algorithm method which can generate the knowledge contained in the customer's transaction data, regarding the purchase pattern by the consumer. Based on the calculation of apriori algorithm that meets the minimum value of confidence and tested with Tanagra software, the highest Indomaret rule store that appears on Instant Oil and Noodle products with Support value 43.3% and confidence 92.8%, this is the same as manual calculation a priori algorithm. Then can be arranged product layout adjacent to facilitate the existence of the product and make it easier in determining inventory of product promo desired by consumer and can be used as decision Support manager in managing company activity.